Produksi Konten Hari Bumi 2022 pada Reels Instagram - Widya Sekar Dwisari; Angelia Anggieta Putri (Universitas Bumigora, 2023)
Social media is a means to share information, communicate media, build networks and compete with other competitors through content on the Instagram platforms. The role of Social Media Specialists in companies such as PT Aseli Dagadu Djokdja is significant because it has an essential role in handling social media, starting from determining ideas, producing, and publishing content, to activation and collaboration. The work method used by Social Media specialists consists of four stages, namely pre-production (preparation), production (manufacture), post-production (finishing & distribution), and weekly report (data analysis). The data collection techniques are interviews, field observations with participation and non-participation observations, documentation, and literature studies. The project produced include: 'Earth Day 2022' posted on April 22, 2022, on collaborators' Instagram reels @dgdindonesia with @yogyatourium. Therefore, this study focuses on